Micro-nano structure supercapacitor electrode preparation method and all-solid-state supercapacitor
By using a hollow grid structure and a multi-stage micro-nano structure active material in the supercapacitor electrode, the problem of reduced electrochemical performance and light transmittance caused by excessive load of active materials is solved, and high electricity is achieved Chemical properties and good light transmittance.
Patent Information
- Application Number
- CN202411452817.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
AI Technical Summary
Excessive loading of active materials in existing supercapacitor electrodes leads to the problem of reduced electrochemical performance and light transmittance.
A conductive grid gate with a hollow mesh-like structure is used as the current collector electrode skeleton, and a supercapacitor electrode is constructed by electrochemical deposition of multi-stage micro-nano structure active materials.
It realizes high electrochemical performance and good light transmittance of supercapacitor electrodes, while increasing the load of active materials to meet the mechanical performance requirements of complex application scenarios.
Smart Images

Figure CN119446796A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of micro-nano manufacturing technology, and in particular relates to a method for preparing a micro-nano structure supercapacitor electrode and an all-solid-state supercapacitor. Background Art
[0002] As an important new energy storage device in the "dual carbon" economy, supercapacitors can fill the defects of low battery power and insufficient energy density of traditional capacitors that affect energy storage capacity, which is of great significance to green, low-carbon and sustainable development.
[0003] The collector electrodes in current supercapacitors are mostly supported by transparent substrates, such as PET, PE, etc., which are restricted by the transmittance and thickness of the organic transparent substrate. During the deformation process of bending or even folding, the interface contact between the substrate and the conductive material, active material and solid electrolyte will be affected, thus affecting the mechanical stability of the capacitor device.
[0004] For high-performance flexible transparent all-solid-state supercapacitors, the key lies in the design and construction of supercapacitor electrodes. In order to obtain high electrochemical performance, the loading amount of active materials is often directly increased, but when the active material is overloaded, the electrochemical performance and light transmittance of the supercapacitor electrode are easily reduced. Summary of the invention
[0005] The present invention provides a method for preparing a micro-nanostructure supercapacitor electrode and an all-solid-state supercapacitor, so as to solve the problem in the prior art that the electrochemical performance and light transmittance of the supercapacitor electrode are reduced due to excessive loading of active materials.
[0006] In a first aspect, the present invention provides a method for preparing a micro-nanostructure supercapacitor electrode, comprising:
[0007] Preparing a conductive grid with a hollow mesh structure on a conductive substrate;
[0008] Electrochemically active materials are deposited on the conductive grid to obtain micro-nanostructured supercapacitor electrodes.
[0009] In one embodiment of the present invention, the step of preparing a conductive grid having a hollow mesh structure on a conductive substrate comprises:
[0010] spin coating a positive photoresist on a conductive substrate;
[0011] The conductive substrate coated with positive photoresist is exposed graphically by laser direct writing;
[0012] Dissolving the exposed area until the conductive substrate at the bottom of the groove in the exposed area is completely exposed to obtain a patterned grid groove;
[0013] Using selective electrodeposition to induce and constrain the conductive structure to be deposited in the patterned grid grooves to form a conductive grid with a mesh structure;
[0014] The conductive grid is peeled off from the conductive substrate to obtain a conductive grid with a hollow mesh structure.
[0015] In one embodiment of the present invention, the conductive grid is made of a metal material, a carbon-based material or a conductive oxide.
[0016] In one embodiment of the present invention, the conductive grid is in a square, hexagonal, ring or special-shaped structure.
[0017] In one embodiment of the present invention, the step of depositing an electrochemically active material on a conductive grid to obtain a micro-nanostructured supercapacitor electrode comprises:
[0018] A first conductive layer is electrochemically deposited on the conductive grid to serve as a core point of the micro-nano structure;
[0019] The second conductive layer is deposited on the first conductive layer at a preset deposition temperature, a preset deposition voltage and a preset deposition time to obtain a micro-nano structure supercapacitor electrode.
[0020] In one embodiment of the present invention, the electrochemical deposition of a first conductive layer on the conductive grid as a core point of the micro-nano structure comprises:
[0021] Using a mixed solution of 0.1 mol KCl and 0.1 mmol HAuCl4, metallic gold was electrochemically deposited on the conductive grid as the core point of the micro-nano structure.
[0022] In one embodiment of the present invention, the second conductive layer is deposited on the first conductive layer at a preset deposition temperature, a preset deposition voltage and a preset deposition time to obtain a micro-nanostructure supercapacitor electrode, comprising:
[0023] At a preset deposition temperature, a preset deposition voltage and a preset deposition time, a second conductive layer is deposited on the first conductive layer using a mixed solution of 0.05 mol MnSO4 and 0.05 mol CH3COONa to obtain a micro-nanostructure supercapacitor electrode.
[0024] In one embodiment of the present invention, the preset temperature is greater than or equal to 39.5°C and less than or equal to 40.5°C.
[0025] In a second aspect, the present invention provides a supercapacitor electrode prepared by the method for preparing a micro-nanostructure supercapacitor electrode described in the first aspect.
[0026] In a third aspect, the present invention provides an all-solid-state supercapacitor, comprising the supercapacitor electrode described in the second aspect.
[0027] The present invention provides a method for preparing a micro-nano structure supercapacitor electrode and an all-solid-state supercapacitor. In the method, a conductive grid with a hollow mesh structure is used as a current collector electrode skeleton, which effectively avoids the adverse effects of a substrate, has an ultra-thin thickness, and has good mechanical flexibility and light transmittance. At the same time, the hollow structure can provide a larger surface area for subsequent material deposition. On the conductive grid with a hollow mesh structure, multi-level micro-nano structure active materials are further deposited to construct a supercapacitor electrode. The micro-nano structure surface can obtain a larger specific surface area, increase the loading amount of active materials, fully promote electron transfer and ion diffusion, and obtain better electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic diagram of a process for preparing a micro-nanostructure supercapacitor electrode provided by an embodiment of the present invention;
[0030] Figure 2 A flow chart of preparing a conductive grid provided by an embodiment of the present invention;
[0031] Figure 3 A surface morphology of a nickel grid provided in an embodiment of the present invention;
[0032] Figure 4 A morphology of gold particles on a nickel grid / gold composite electrode provided in an embodiment of the present invention;
[0033] Figure 5 The surface morphology of the micro-nanostructured MnO2 provided in the embodiment of the present invention after deposition for 20 seconds;
[0034] Figure 6 The surface morphology of the micro-nanostructured MnO2 provided in the embodiment of the present invention after being deposited for 40 seconds;
[0035] Figure 7 A surface morphology of the micro-nanostructured MnO2 when deposited for 80 seconds provided in an embodiment of the present invention;
[0036] Figure 8 A surface morphology of the micro-nanostructured MnO2 when deposited for 120 seconds provided in an embodiment of the present invention;
[0037] Fig. 9A supercapacitor electrode morphology of MnO2 deposited at elevated temperature for 80 seconds provided in an embodiment of the present invention;
[0038] Fig.10 for Fig. 9 Corresponding detail diagram;
[0039] Fig.11 A supercapacitor electrode morphology of MnO2 deposited at room temperature for 80 seconds provided in an embodiment of the present invention;
[0040] Fig.12 for Fig.11 Corresponding detail diagram;
[0041] Fig.13 CV curves corresponding to the electrode with a flat surface deposited at room temperature provided by the embodiment of the present invention at scan rates of 0.1 V / s, 0.05 V / s, 0.01 V / s and 0.005 V / s;
[0042] Fig.14 CV curves corresponding to the electrode with micro-nano structure deposited by increasing temperature provided by the embodiment of the present invention at scan rates of 0.1 V / s, 0.05 V / s, 0.01 V / s and 0.005 V / s;
[0043] Fig.15 A comparison diagram of area capacitance provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The present invention obtains an active material layer with a micro-nano structured surface by controlling the active material deposition conditions. Compared with an active material layer with a smooth surface, the active material with a micro-nano structure has a larger surface area, a larger contact area with the electrolyte, and more complete ion transmission, thereby having better electrochemical performance.
[0046] Example 1
[0047] like Figure 1 As shown, this embodiment provides a method for preparing a micro-nanostructure supercapacitor electrode, comprising:
[0048] Step 101: Prepare a conductive grid with a hollow mesh structure on a conductive substrate.
[0049] In this embodiment, the conductive grid is made of metal material, carbon-based material or conductive oxide. The conductive grid structure can be square, hexagonal, annular, or special-shaped. The hollow collector electrode has good light transmittance, flexibility and conductivity. This embodiment is described by taking the conductive grid material of metal nickel as an example. Figure 2 As shown, this step includes:
[0050] The positive photoresist is spin-coated on the conductive substrate. In this embodiment, the material of the conductive substrate includes but is not limited to indium tin oxide.
[0051] Laser direct writing is used to perform patterned exposure on a conductive substrate coated with positive photoresist. After exposure, the physical properties of the positive photoresist change and it becomes soluble in the developer, while the unexposed area is insoluble in the developer.
[0052] Combined with the developing technology, the exposed area is dissolved until the conductive substrate at the bottom of the groove in the exposed area is completely exposed, thereby obtaining a patterned mesh groove. The bottom of the patterned mesh groove is exposed indium tin oxide glass.
[0053] Selective electrodeposition is used to induce and constrain the deposition of conductive structures in the patterned grid grooves to form a conductive grid with a mesh structure. The deposition time can be controlled to avoid a reduction in light transmittance caused by a deposition thickness exceeding the groove thickness. For example, a conductive grid with a thickness of 4 μm nickel can be deposited.
[0054] The conductive grid is peeled off from the conductive substrate to obtain a conductive grid with a hollow mesh structure. The nickel grid / photoresist / indium tin oxide glass is placed in a high-concentration developer to remove the remaining photoresist, and the nickel grid is peeled off from the indium tin oxide glass after cleaning to obtain a hollow self-supporting nickel grid electrode, that is, a conductive grid with a hollow mesh structure.
[0055] A hollow self-supporting conductive grid is used as the current collector electrode skeleton. Based on this current collector electrode, a suitable deposition method is selected to deposit electrochemically active materials such as transition metal oxides, two-dimensional metal carbides, graphene, etc. on the current collector electrode. In this process, it is necessary to control the active material deposition conditions to obtain an active material layer with a micro-nanostructure surface morphology, so as to obtain a flexible and transparent micro-nanostructure supercapacitor electrode.
[0056] Step 102: depositing electrochemically active materials on the conductive grid to obtain a micro-nanostructured supercapacitor electrode.
[0057] In this embodiment, on the self-supporting nickel grid prepared above, active materials on the surface of multi-level micro-nano structures are prepared by electrochemical deposition, such as Figure 3As shown. The surface of the self-supporting nickel grid was electrochemically deposited with metallic gold, the deposition solution was a mixed solution of 0.1 mol KCl and 0.1 mmol HAuCl4, the deposition parameters were -0.5 V, 5 sec and 0 V, 100 sec, the surface morphology of the deposited gold particles was as shown Figure 4 As shown, the deposited gold is about 100 nanometers in size and is evenly distributed on the surface of the nickel grid, which can improve the conductivity of the electrode and provide nucleation points for subsequent micro-nano structures. Subsequently, on the basis of the nickel grid / gold electrode, the active material with micro-nano structure is deposited by increasing the temperature. The deposition solution is a mixed solution of 0.05 moles of MnSO4 and 0.05 moles of CH3COONa, the deposition temperature is 40°C, and the deposition voltage is 0.92V. The deposition time is controlled here to obtain the best micro-nano structure. Figure 5 , Figure 6 , Figure 7 and Figure 8 The surface morphologies of the micro-nanostructured MnO2 were shown when deposited for 20 seconds, 40 seconds, 80 seconds and 120 seconds respectively. It can be seen that as the deposition time increased to 80 seconds, the coverage of the microstructured MnO2 gradually increased and the surface area increased, but when the deposition continued to 120 seconds, the micro-nanostructure was overly deposited and covered, and the surface area decreased sharply.
[0058] In this embodiment, the deposition time is selected as 80 seconds to construct a multi-level micro-nanostructure MnO2 / Au / Ni supercapacitor electrode. Fig. 9 The morphology of the micro-nanostructure electrode shown in FIG. 1 shows that the micro-nanostructure is evenly covered on the surface of the self-supporting Ni / Au electrode, completely wrapping the entire wire grid. Fig.10 As shown in the figure, the smaller size details of the corresponding electrode morphology. For comparison, MnO2 was also deposited at room temperature, such as Fig.11 The surface morphology of the electrode deposited with MnO2 at room temperature is shown in the figure. Fig.12 for Fig.11 From the corresponding detailed image, we can see that the deposited MnO2 has a dense structure and a flat surface. The supercapacitor electrode with micro-nano structure has a larger surface area. Figure 9-12 It can be seen that the entire upper surface, lower surface and side wall of the self-supporting electrode can be used to deposit MnO2, providing a larger deposition area.
[0059] This example further tests the electrochemical properties of the micro-nanostructure supercapacitor electrode by using a liquid test method with 1 mole of NaSO4 as the electrolyte to test its liquid electrochemical properties. At the same time, as a comparison, a supercapacitor electrode with a smooth surface deposited at room temperature is tested. The corresponding current-voltage curve (i.e., CV curve) is tested by cyclic voltammetry. Fig.13 and Fig.14It can be seen that at the same scan rate, the area enclosed by the CV curve of the supercapacitor with micro-nano structure is larger than the area protected by the CV curve of the supercapacitor electrode with smooth surface. Further, the area capacitance corresponding to each of the two electrodes is calculated, as shown in Fig.15 As shown in the figure, the area capacitances corresponding to the CV curves of the electrode with a flat surface deposited at room temperature and the electrode with a micro-nano structure deposited at elevated temperature at scan rates of 0.1V / s, 0.05V / s, 0.01V / s and 0.005V / s are obtained, that is, the area capacitances corresponding to different scan rates are obtained. It can be seen intuitively that at different scan rates, the area capacitances of the micro-nano structure supercapacitor electrodes are twice the area capacitances of the smooth supercapacitor electrodes deposited at room temperature. It can be seen that the micro-nano structure surface effectively improves the electrochemical performance of the supercapacitor electrodes.
[0060] In summary, in the method for preparing the micro-nanostructure supercapacitor electrode provided in this embodiment, the self-supporting current collector electrode does not require substrate support. The supercapacitor electrode constructed in this way has higher light transmittance, flexibility and ultra-thin thickness than the electrode with a substrate, and can meet the needs of conformable attachment and mechanical properties (bending, folding, etc.) in complex application scenarios.
[0061] The hollowed-out current collector electrode has a large surface area, and its upper surface, lower surface and sidewalls can all be used for the deposition of active materials, which can increase the loading amount of active materials and thus increase the electrochemical energy storage capacity.
[0062] Precisely controlling the multi-level micro-nano morphology of the deposited active materials can effectively increase the contact area with the electrolyte, expand the electron transmission and ion diffusion paths, and obtain better electrochemical performance.
[0063] The hollowed-out supercapacitor electrode is thin and light with high optical transmittance. At the same time, both the hollowed-out self-supporting nickel grid electrode and the micro-nanostructured MnO2 provide a large surface area for the supercapacitor electrode, effectively enhancing the electrochemical performance of the supercapacitor electrode.
[0064] Example 2
[0065] This embodiment provides a supercapacitor electrode, which is prepared by the method for preparing a micro-nanostructure supercapacitor electrode provided in Embodiment 1.
[0066] Example 3
[0067] This embodiment provides an all-solid-state supercapacitor, including the supercapacitor electrode provided in Embodiment 2.
[0068] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a micro-nanostructure supercapacitor electrode, characterized in that: include: Preparing a conductive grid with a hollow mesh structure on a conductive substrate; Electrochemically active materials are deposited on the conductive grid to obtain micro-nanostructured supercapacitor electrodes.
2. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 1, characterized in that: The method of preparing a conductive grid with a hollow mesh structure on a conductive substrate comprises: spin coating a positive photoresist on a conductive substrate; The conductive substrate coated with positive photoresist is exposed graphically by laser direct writing; Dissolving the exposure area until the conductive substrate at the bottom of the groove in the exposure area is completely exposed to obtain a patterned grid groove; Using selective electrodeposition to induce and constrain the conductive structure to be deposited in the patterned grid grooves to form a conductive grid with a mesh structure; The conductive grid is peeled off from the conductive substrate to obtain a conductive grid with a hollow mesh structure.
3. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 1, characterized in that: The conductive grid is made of metal material, carbon-based material or conductive oxide.
4. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 1, characterized in that: The conductive grid is in the shape of a square, hexagon, ring or special-shaped structure.
5. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 1, characterized in that: The electrochemically active material is deposited on the conductive grid to obtain a micro-nanostructure supercapacitor electrode, comprising: A first conductive layer is electrochemically deposited on the conductive grid to serve as a core point of the micro-nano structure; The second conductive layer is deposited on the first conductive layer at a preset deposition temperature, a preset deposition voltage and a preset deposition time to obtain a micro-nano structure supercapacitor electrode.
6. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 5, characterized in that: The electrochemical deposition of a first conductive layer on the conductive grid as a core point of the micro-nano structure comprises: Using a mixed solution of 0.1 mol KCl and 0.1 mmol HAuCl4, metallic gold was electrochemically deposited on the conductive grid as the core point of the micro-nano structure.
7. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 5, characterized in that: The method of depositing a second conductive layer on the first conductive layer at a preset deposition temperature, a preset deposition voltage and a preset deposition time to obtain a micro-nanostructure supercapacitor electrode comprises: At a preset deposition temperature, a preset deposition voltage and a preset deposition time, a second conductive layer is deposited on the first conductive layer using a mixed solution of 0.05 mol MnSO4 and 0.05 mol CH3COONa to obtain a micro-nanostructure supercapacitor electrode.
8. The method for preparing a micro-nanostructure supercapacitor electrode according to claim 7, characterized in that: The preset temperature is greater than or equal to 39.5° C. and less than or equal to 40.5° C.
9. A supercapacitor electrode, characterized in that: The supercapacitor electrode is prepared by the method for preparing the micro-nanostructure supercapacitor electrode according to any one of claims 1 to 8.
10. An all-solid-state supercapacitor, characterized in that: Comprising the supercapacitor electrode as claimed in claim 8.